The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s1517-83822014000300007
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of allylic thiocyanates derived from the Morita-Baylis-Hillman reaction

Abstract: Bacterial resistance to commonly used antibiotics has been recognized as a significant global health issue. In this study, we carried out the screening of a family of allylic thiocyanates for their action against a diversity of bacteria and fungi with a view to developing new antimicrobial agents. Allylic thiocyanates bearing halogenated aryl groups, which were readily obtained in two steps from the Morita-Baylis-Hillman adducts, showed moderate-to-high activity against selective pathogens, including a methici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
4
5
0
Order By: Relevance
“…Previous data showed that compound 11 exhibited moderate‐to‐good activity against C. albicans (12.5 μmol L −1 ) and C. tropicalis (25 μmol L −1 ); these findings corroborate to our results. Furthermore, compounds 8 , 9 , 11 and 14 inhibited MRSA growth, and thus demonstrated a broad spectrum of action against fungi and bacteria.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previous data showed that compound 11 exhibited moderate‐to‐good activity against C. albicans (12.5 μmol L −1 ) and C. tropicalis (25 μmol L −1 ); these findings corroborate to our results. Furthermore, compounds 8 , 9 , 11 and 14 inhibited MRSA growth, and thus demonstrated a broad spectrum of action against fungi and bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…Previous data showed that compound 11 exhibited moderate‐to‐good activity against C. albicans (12.5 μmol L −1 ) and C. tropicalis (25 μmol L −1 ); these findings corroborate to our results. Furthermore, compounds 8 , 9 , 11 and 14 inhibited MRSA growth, and thus demonstrated a broad spectrum of action against fungi and bacteria. Compound 11 and bromo‐substituted analogues 8 and 9 exhibited promising antitubercular activity against replicating and non‐replicating forms of Mtb H 37 Rv (MIC 0.25 μmol L −1 ) with relatively low toxicity toward VERO cells .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was shown that a piperidine isoselenocyanate derivative is the most active among its isosters against selected fungi, including Fusarium culmorum . Furthermore, related thiocyanates exhibit a variety of biological properties,, including antibacterial activity against Mycobacterium tuberculosis and methicillin‐resistant Staphylococcus aureus (MRSA) . These facts motivate the investigation of allylic organoselenium compounds as antifungal agents.…”
Section: Introductionmentioning
confidence: 99%